Toxic Leadership and Job Satisfaction in the Middle Eastern Education Sector: The Influence of Organizational Culture and Trust - Fida Ragheb Hassanein; Samaneh Mohammadi; Pouya Zargar (Administrative Sciences)
Toxic leadership has profound implications for employees’ psychological wellbeing, particularly in academia, as a supportive workplace is crucial for intellectual prosperity and growth. In various parts of the Middle East, toxic leadership has been a major element in suppressing academic freedom, low levels of creativity, and innovation backed with favoritism, nepotism, and lack of support. This study examines the detrimental effects of toxic leaders on academic staff’s job satisfaction among academic staff in Middle Eastern universities. Grounded in the social learning theory, leader–member exchange theory, and conservation of resources theory, this research examines the mediating effect of organizational culture and trust in leaders. A quantitative approach using partial least squares—structural equation modeling with Smart-PLS software Version 3—was deployed on survey data from 236 faculty members and academic administrators across 11 universities in the region. The results show that toxic leadership significantly reduces job satisfaction, which is better explained by key mediating elements of organizational culture and trust in leaders. The findings highlight the need for fostering a culture of trust, leadership development, and transparent strategies to enhance the academic workplace for the staff and improve the dynamic and performance of the educational environment in the region. This study provides practical recommendations for mitigating toxic leadership in the education sector of the Middle East through empirically validating its detrimental effects on the psychological wellbeing of academic staff, which is a major element that barriers significant academic achievements.